IMPACT OF CLIMATE CHANGE ON Pinus hartwegii Lindl. FOREST ECOSYSTEMS AS A SUBJECT OF INTERINSTITUTIONAL AND INTERNATIONAL STUDIES - Pérez-Suárez, Marlín; Ramírez-Albores, Jorge Enrique; Vargas-Hernández, J. Jesús; Rozenberg, Philippe (Agrociencia (Montecillo), 2025)
Pinus hartwegii Lindl. is a low-temperature-adapted species that forms the highest elevation tree lines in the world, reflecting its tolerance to extreme high mountain conditions. Studying the mechanisms that determine the variation of tree lines in different regions helps to more accurately assess the impact of climate change on forest ecosystems. Thus, assessing its impact on the ecological features that affect P. hartwegii is critical, as is identifying and defining information gaps that may lead to new, important, and significant research lines. In this work, an intensive literature search on the impact of climate change on P. hartwegii was carried out in Scopus and other specialized databases. The information was grouped and analyzed in VOSviewer by year of publication, institution, research topics, and study area. Scientific publications on P. hartwegii have increased exponentially since its first publication, reaching a total of 281 scientific papers until 2024. More than 66 % of all studies were conducted in protected areas such as Iztaccíhuatl-Popocatépetl, Nevado de Toluca, and Cofre de Perote in Mexico. The most studied topics were forest management, climate change, dendrochronology, and population dynamics. The high heterogeneity in the number of studies suggests that there is an uneven distribution of interinstitutional and international resources or research interests. This study highlights the need to intensify research on the ecology and biology of the species, as well as to foster inter-institutional collaboration and coordination to increase studies in specific areas to deepen the understanding of the adaptive capacity of P. hartwegii populations in the face of the current climate crisis.